(untitled) (Journal of Surgical Sciences, 2020)
Ewing’s sarcoma is the second most common highly malignant primary mesenchymal bone tumor of childhood and adolescence affecting mainly the diaphysis of long and flat bones. This tumor is extraordinarily rare in small bones of the hand and presents as a swelling with atypical radiological features of cystic and lytic lesion with scanty periosteal reaction. Prognosis is greatly influenced by the presence of metastasis at presentation, further emphasizing the importance of early diagnosis. Multimodality treatment using surgery, radiotherapy and chemotherapy is currently recommended though no consensus exists. We report a case of Ewing’s sarcoma of the 5th metacarpal bone in 40 years old lady which was initially missed and so there was delayed onset of treatment. Journal of Surgical Sciences (2018) Vol. 22 (1) : 70-72